Possible surgical complications of the zygomatic implant in oro-facial reconstructive surgery: A systematic review - Heron Gezahegn Gebretsadik (Orapuh Journal, 2021)
Dental implants are widely used in oro-facial rehabilitation. They are considered effective and acceptable in the replacement of lost teeth and, with an implant-supported prosthesis, oro-facial soft and hard tissues configuration. A zygomatic implant is a class of dental implant, which is different from the conventional one, mainly, because it is much longer and attached to the zygomatic bone instead of the maxillary bone. This systematic review was aimed at identifying the possible frequent surgical complications of zygomatic implants in oro-facial reconstructive surgery. A review of published literature with no time limitation was conducted in November 2019. An electronic search of PubMed, ISI Web of Science, Cochrane, and Google Scholar databases was conducted to obtain information for this review. A total of 29 prospective and retrospective studies, which contained relevant information, were considered for data extraction and analysis. Based on the information obtained from the included articles, a total of 3613 zygomatic implants were placed in 1679 study participants. This translates to 2.2 implants being placed per single cohort. After an average follow-up period of 3.5 years, the most frequently reported surgical complications were sinus infection (65.5%), soft tissue trauma (8%), mucositis (7%), hematoma (5%), paraesthesia (4%), and non-osteointegration (3%). Peri-implantitis, oroantral communication, fistula, and sinus membrane perforation comprised of 2%, 1.2%, 1.1%, and 1% reported complications respectively. Intracerebral penetration, aspergillosis, rhinosinusitis, otitis, orbital cavity penetration, and persistent pain together comprised 2.2% of all the reported zygomatic implant-related surgical complications. The ZI procedure is associated with various complications which, although rare, may jeopardize the treatment plan. The set of complications identified in this study may underestimate the overall situation. Therefore, the installation of more studies with longer follow-up periods and larger study participants may be necessary to enhance the scientific evidence of the possible surgical complications of this treatment modality.